Violencia intrafamiliar y su influencia en el trastorno negativista en un niño de 9 años de edad - Ordoñez Marcillo, Mercedes Guadalupe (2020)
The present case study is focused on publicizing how a family that presents domestic violence influences a child's behavior, physical and psychological violence and family breakdown in a home cause great damage to the child's integrity. For this study we will use direct observation, psychological interview, psychometric and projective tests, clinical history and the DSM-5 manual that will be used to diagnose the child with the challenging negativist disorder, it is worth mentioning that this research was carried out in the Educational Unit “ José María Estada Coello ”to a student of 4th year of basic education, El Mamey citadel, Babahoyo canton. For the therapeutic approach to the problem, the cognitive-behavioral approach was used to structure the family and reduce the child's challenging behavior.